2020
DOI: 10.3389/fped.2020.00055
|View full text |Cite
|
Sign up to set email alerts
|

The Extremely Preterm Infant: Ethical Considerations in Life-and-Death Decision-Making

Abstract: Care of the preterm infant has improved tremendously over the last 60 years, with attendant improvement in outcomes. For the extremely preterm infant, <28 weeks' gestation, concerns related to survival as well as neurodevelopmental impairment, have influenced decision-making to a much larger extent than seen in older children. Possible reasons for conferring a different status on extremely preterm infants include: (1) the belief that the brain is a privileged organ, (2) the degree of medical uncertainty in ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 42 publications
(56 reference statements)
1
21
0
Order By: Relevance
“…Although the patients in this study had quite a high mortality rate, we expect our medical challenges to produce better prognosis in this population as the limit of viability gradually decreases. De ning these limits is important for developing local guidelines that will provide standards of practice to improve the morbidity and mortality of ELBW infants and for counseling parents [39]. Therefore, we hope that our study would be useful for developing local guidelines to both support health care practitioners and provide consistency of care for extremely preterm infants.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Although the patients in this study had quite a high mortality rate, we expect our medical challenges to produce better prognosis in this population as the limit of viability gradually decreases. De ning these limits is important for developing local guidelines that will provide standards of practice to improve the morbidity and mortality of ELBW infants and for counseling parents [39]. Therefore, we hope that our study would be useful for developing local guidelines to both support health care practitioners and provide consistency of care for extremely preterm infants.…”
Section: Discussionmentioning
confidence: 97%
“…Since these infants may face various disabilities, chronic illnesses, multiple surgeries, and severe care dependency, deciding whether to resuscitate is both a clinical and an ethical decision [38]. A recent study has reported the degree of medical uncertainty and the fact that parents will deal with the consequences of decision making, highlighting the importance of providing a wide range of discretion in parental decision-making authority [39]. However, neonatologists are unable to determine the individual prognosis at birth and resuscitation has to be provided quickly for it to be successful.…”
Section: Discussionmentioning
confidence: 99%
“…Since these infants may face various disabilities, chronic illnesses, multiple surgeries, and severe care dependency, deciding whether to resuscitate is both a clinical and an ethical decision [ 38 ]. A recent study has reported the degree of medical uncertainty and the fact that parents will deal with the consequences of decision making, highlighting the importance of providing a wide range of discretion in parental decision-making authority [ 39 ]. However, neonatologists are unable to determine the individual prognosis at birth and resuscitation has to be provided quickly for it to be successful.…”
Section: Discussionmentioning
confidence: 99%
“…Although the patients in this study had quite a high mortality rate, we expect our medical challenges to produce better prognosis in this population as the limit of viability gradually decreases. Defining these limits is important for developing local guidelines that will provide standards of practice to improve the morbidity and mortality of ELBW infants and for counseling parents [ 39 ]. Therefore, we hope that our study would be useful for developing local guidelines to both support health care practitioners and provide consistency of care for extremely preterm infants.…”
Section: Discussionmentioning
confidence: 99%
“…Since these infants may face various disabilities, chronic illnesses, multiple surgeries, and severe care dependency, deciding whether to resuscitate is both a clinical and an ethical decision [38]. A recent study has reported the degree of medical uncertainty and the fact that parents will deal with the consequences of decision making, highlighting the importance of providing a wide range of discretion in parental decision-making authority [39].…”
Section: Discussionmentioning
confidence: 99%